THU0028 AN EXPLANTION FOR HOW VIRAL INFECTION MAY TRIGGER SPONDYLOARTHROPATHY BASED ON TLR9 DRIVEN TNF RESPONSES FROM ENTHESEAL DERIVED PLASMACYTOID DENDRITIC CELLS. (2nd June 2020) - Zhou, Q.; Vadakekolathu, J.; Sharif, K.; Russell, T.; Rowe, H.; Millner, P.; Loughenbury, P.; Rao, A. S.; Dunsmuir, R.; Bridgewood, C.; El-Sherbiny, Y.; Mcgonagle, D.
Abstract : Background: It is well known that viral infections may trigger psoriatic arthritis (PsA), a disease that typically has extensive pre-clinical entheseal abnormalites. Skin resident plasmacytoid dendritic cells (pDCs) produce IFNα that contribute to T cell expansion and the development of experimental psoriasis [1, 2]. IFN pathway SNPs have been reported in both PsA and psoriasis and we previously reported the presence of pDCs at the human enthesis [3]. Objectives: To investigate whether the TLR9 agonist ODN that replicates viral infection activate a wide array of of entheseal derived pDCs molecular cascades including the TNF pathway that might provide a link between viral infection and PsA. Methods: pDCs were sorted from enthesis and blood and stimulated with ODN as previously described (n=16) [3, 4]. IFNα protein pre and post stimulation were detected by ELISA. Intracellular flow cytometry (IFC) of entheseal pDCs was used to detect TNF protein. RNA was extracted post-stimulation. The mRNA were hybridised and tagged by probes then measured on the nCounter platform. Data was analysed using nSolver 4.0. Log2 |fold change| >1 and P-value <0.05 were considered statistically significant. The gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) of differentially expressed genes (DEGs) were analyzed using DAVID. Protein-protein interaction (PPI) network was drawn by STRING. Results: Stimulated entheseal pDCs showed a strong DEGs pattern pointing towards increased TNF expression. There were 11 genes significantly upregulated including TNF. RIPK3 is involved in TNF signalling pathway. TNF, RIPK3 and ZBP1 are involved in necroptosis. TNF and ITGB2 are involved in IL-4 and IL-13 signaling pathway. TNF, HLA-DOA, ITGB2/TLR7 are involved in virus infection. Together it highlights extremely activated TNF pathway genes. IFN protein was induced in sorted entheseal pDCs following stimulation (n=8). TNF protein was detected by IFC on stimulated entheseal pDCs (CD45+HLA-DR+CD123+CD303+ CD11c-) (n=3). We also compared entheseal and matched peripheral blood pDCs (n=8) following stimulation where no major differences in the TNF pathway were present between groups. The KEGG analysis was mapped in Figure 1 . GO analysis showed the most significant change in biological processes was enriched in the positive regulation of DNA binding transcription factor activity. The change in molecular function was mainly enriched in p53 binding. Conclusion: Entheseal pDCs, upon viral molecule stimulation, show several markers of activation. However, TNF pathway genes were highly activiated which provides a novel mechanistic link between viral infection and PsA as reported in epidemiological studies. References: [1]Nestle, F.O., et al., Plasmacytoid predendritic cells initiate psoriasis through interferon-alpha production. J Exp Med, 2005. 202 (1): p. 135-43. [2]Christophers, E., et al., The risk of psoriatic arthritis remains constant following initial diagnosis of psoriasis among patients seen in European dermatology clinics. J Eur Acad Dermatol Venereol, 2010. 24 (5): p. 548-54. [3]Zhou, Q., PLASMACYTOID DENDRITIC CELLS IN THE ENTHESIS: PHENOTYPING AND FUNCTION INVESTIGATION. Annals of the Rheumatic Diseases, 2019. 78 . [4]Bridgewood, C., et al., Identification of myeloid cells in the human enthesis as the main source of local IL-23 production. Ann Rheum Dis, 2019. 78 (7): p. 929-933. Disclosure of Interests: Qiao Zhou: None declared, Jayakumar Vadakekolathu: None declared, Kassem Sharif: None declared, Tobias Russell Grant/research support from: Novartis UK Investigator Initiated non-clinical research funding support, Hannah Rowe Grant/research support from: Novartis UK Investigator Initiated non-clinical research funding support, Peter Millner: None declared, Peter Loughenbury: None declared, Abhay S Rao: None declared, Robert Dunsmuir: None declared, Charlie Bridgewood: None declared, Yasser El-Sherbiny: None declared, Dennis McGonagle Grant/research support from: Janssen Research & Development, LLC